Whistleblowing Intention Among Government Financial Officers in Indonesia - Adila Restu Adha; Rizqa Anita (Sekolah Pascasarjana Universitas Lancang Kuning, 2021)
The purpose of this study is to explore and develop a comprehensive model of internal whistleblowing intention. Specifically, this study examines the effect of authentic leadership on internal whistleblowing intention. Furthermore, this study aims to investigate the effect of authentic leadership on internal whistleblowing intention through personal identification and organizational commitment. To test the hypotheses, a partial least square analysis is applied to questionnaire survey data from 196 employees in Indonesia. As hypothesized, the result revealed that authentic leadership influences the internal whistleblowing intention. In addition, the result also indicates that authentic leadership has an indirect effect on internal whistleblowing intention through personal identification and organizational commitment. The implications of these findings are thoroughly discussed in this study.